Estimation of nitrogen dioxide levels on streets from Fortaleza Brazil using passive sampling and multivariate analysis - de Sousa, Francisco Wagner; Maia, Maxwell Lima; Quintanilha, Wendy Fernandes Lavigne; Cassiano, Demostenis Ramos; Bertoncini, Bruno Vieira; Nascimento, Ronaldo Ferreira; Oliveira, Cleidiane Silva; Ribeiro, Jefferson Pereira (Eclética Química, 2024)
The increase in the fleet of motor vehicles circulating in urban centers is one of the main generators of gaseous pollutants harmful to human health and the environment. Pollutants can be economically and effectively monitored through passive sampling. This study aims to estimate NO2 levels on roads of Fortaleza city /CE using the passive sampling method. 12 campaigns covered the rainy (March-June) and the dry (July-November) seasons in 2019. The seasonal averages of NO2 in the rainy season were higher than the dry one, and Almirante Rubim Street showed the greatest difference in the averages: 26.6 µg m-3 in the rainy and 19.3 µg m-3 in the dry season. The principal component analysis applied to the averages of NO2 concentration in the rainy and dry seasons, vehicle traffic and Height of the road/width ratio indicated that components 1, 2 and 3 explain 94.4% of the studied cases. Passive sampling proved to be efficient, contributing to the production of unpublished data about NO2 levels in streets of Fortaleza/Ceará/Brazil from mobile sources.